Rational design of new chemical drugs based on compounds that block the pores in cell membranes - Kakpenova, A.; Zhanbossinova, A.; Negmetzhanov, B.; Tauanov, Z.; Karginov, V.; Adilov, S.; Alibek, K. (Nazarbayev University, 2013)
“Rational Drug Design” method is a new principle and methodology in producing pharmaceuticals based on precise and structure-oriented approach. The proposed method is based on principle of blocking the pores caused by Staphylococccus aureus (S. aureus) toxins in the membranes of host cells [1]. Design of β-cyclodextrin derivatives with precise geometry might be used for production of antibacterial and prophylactic pharmaceuticals against S. aureus infection.
Keywords: first research week; chemical drugs; pharmaceuticals; Staphylococccus aureus infection